Condensed Bridgehead Nitrogen Heterocyclic System: Microwave Assisted Synthesis and Bioactivity of s-Triazolo[3,4-b][1,3,4]thiadiazoles, s-Triazolo[3,4- b][1,3,4]thiadiazines and s-Triazolo [3',4':2,3]thiadiazino[5,6-b]quinoxaline - Raju, R.R.R.K.; Reddy, T.M.; Chakravarthy, A.K. (Asian Journal of Chemistry, 2010)
N-[3-(4-Amino-5-mercapto-4H-[1,2,3]triazol-3-yl)-4,5,6,7-tetrahydro-benzo[b] thiophen-2- yl]benzamide (1) on condensation with chloroacetic acid, a-haloketone and benzoin furnishes [1,2,4]triazolo[3,4-b][1,3,4]thiadiazine derivatives (2), (3) and (4) respectively, while condensation with 2,3-dichloroquinoxaline, carbon disulphide, aromatic carboxylic acid and aromatic carboxaldehydes yield the cyclic products, [1,2,4] triazolo[3,4-b][1,3,4]thiadiazole derivatives (5), (6), (7), (8) respectively. The compounds have been characterized on the basis of elemental analysis and spectral data. The antibacterial, antifungal and antitubercular activities of the compounds have also been evaluated.